FORMATION OF THE CULTURE OF POSITIVE PARENTING PRACTICES AS AN ESSENTIAL COMPONENT OF FAMILY EDUCATION IN THE CONTEXT OF POSTMODERN PEDAGOGY - CUZNEȚOV, Larisa (Acta et Commentationes, Sciences of Education, 2020)
The study contains a small insight centered on the conditions and specifics of the formation of positive parenting culture, approached as a component of family education. The formation of the culture of positive parenting practices was achieved through the school-family-community partnership.The author proposes the Pedagogical Model centered on the quality education of pupils and parents; the postulates of quality education of pupils and parents; exposes parenting skills necessary to form a culture of positive parenting practices; some strategies and ways / ways of capitalizing on the educational partnership, focusing on the quality education of pupils and parents.